Smoke and heat accelerate and increase germination in fire‐prone temperate grassy ecosystems. Issue 12 (9th December 2021) - Hodges, Joshua A.; Price, Jodi N.; Nicotra, Adrienne B.; Neeman, Teresa; Guja, Lydia K.
Abstract: Fire increases seedling recruitment by reducing competition for space and resources. As such, many species in fire‐prone ecosystems germinate in response to fire cues such as smoke and heat. A notable exception is fire‐prone temperate grassy ecosystems, where >20 yr of research has found that fire‐cued germination is rare. We tested the hypothesis that fire cues promote germination in temperate grassy ecosystems of south‐eastern Australia. We treated seeds of 55 common species with smoke, heat, and a combination of smoke and heat and tracked germination over time. We analyzed the effect of all combinations of treatments on germination speed and percent germination. Interestingly, we found that smoke and heat combined—which is more ecologically relevant to an actual fire than smoke and heat alone—was needed to increase germination speed, a mostly unstudied component of the germination ecology of grassy ecosystems. Smoke alone increased percent germination. Both plant family and seed traits influenced the germination response to smoke and heat. Poaceae species were the most responsive (in both speed and percent germination) to smoke alone. Water permeability of the seed coat was a key determinant of whether species responded to heat alone, smoke alone, or combined smoke and heat. Species with water‐impermeable seed coats responded to heat alone for both speed and percent germination. Species with water‐permeable seed coats germinated faster in response to combined smoke and heat and percent germination was increased by smoke alone. In contrast with more than two decades of research—our study of this large and representative group of species demonstrates that fire (via smoke and heat) is an important germination cue in fire‐prone temperate grassy ecosystems of south‐eastern Australia.